2013
DOI: 10.7744/cnujas.2013.40.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in fatty acid composition in various parts of broccoli cultivars

Abstract: :To evaluate seasonal variation in fatty acid composition in broccoli, 12 commercial cultivars of broccoli were grown in spring and fall season at the field of NIHHS, and their floret, leaf and stem parts were used for the fatty acid composition analyses. Among 14 fatty acids detected in broccoli, linolenic, palmitic and linoleic acids were major fatty acids comprising more than 80% of total fatty acids in both the seasons and all the parts. Likewise, stearic and oleic acids were also present in considerable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…In our study, the content of fatty acids in BLP and experimental pasta products was evaluated and respective results are presented in Table 4. Eleven fatty acids were identified in BLP with γ-linoleic acid (C18:3 n6) and C16:0 being the major acids, followed by trans-heptadecenoic acid (C17:1 trans), C18:2 and C18:3 n3, which is in agreement with previous reports [Bhandari et al, 2013;Joon Lee et al, 2009]. Similarly to other authors, PUFA were found to dominate in the analysed BLP.…”
Section: Fatty Acid Profilesupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the content of fatty acids in BLP and experimental pasta products was evaluated and respective results are presented in Table 4. Eleven fatty acids were identified in BLP with γ-linoleic acid (C18:3 n6) and C16:0 being the major acids, followed by trans-heptadecenoic acid (C17:1 trans), C18:2 and C18:3 n3, which is in agreement with previous reports [Bhandari et al, 2013;Joon Lee et al, 2009]. Similarly to other authors, PUFA were found to dominate in the analysed BLP.…”
Section: Fatty Acid Profilesupporting
confidence: 91%
“…Broccoli does not belong to oil crops; however, also contains fatty acids. Leaves of broccoli were found to have the highest compositional ratio of polyunsaturated fatty acid (PUFAs) among all its aerial parts, with linolenic (C18:3 n3), palmitic (C16:0) and linoleic (C18:2) acids being the most dominant, accounting for around 80% of total fatty acids [Bhandari et al, 2013]. In our study, the content of fatty acids in BLP and experimental pasta products was evaluated and respective results are presented in Table 4.…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…Lipids and, in particular, FAs in broccoli have not been extensively discussed in the literature, as they are minor broccoli constituents. In the existing reports, FAs are extracted from broccoli either through conventional solvent extraction [ 13 , 14 ], soxhlet extraction [ 15 , 16 ], or supercritical fluid extraction (SFE), which is a more environmentally friendly approach [ 17 ]. Generally, FAs are characterized as methyl esters (FAMES) using gas chromatography (GC) coupled to flame ionization (FID) [ 13 , 14 , 15 , 18 ], or mass spectrometry (MS) detectors [ 16 , 17 ], though UPLC-MS/MS was recently utilized for a metabolomics analysis of broccoli seeds and sprouts, including FAs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the existing reports, FAs are extracted from broccoli either through conventional solvent extraction [ 13 , 14 ], soxhlet extraction [ 15 , 16 ], or supercritical fluid extraction (SFE), which is a more environmentally friendly approach [ 17 ]. Generally, FAs are characterized as methyl esters (FAMES) using gas chromatography (GC) coupled to flame ionization (FID) [ 13 , 14 , 15 , 18 ], or mass spectrometry (MS) detectors [ 16 , 17 ], though UPLC-MS/MS was recently utilized for a metabolomics analysis of broccoli seeds and sprouts, including FAs [ 19 ]. In most cases, research studies focus on the FA composition of florets, sprouts, and seeds, while there have been limited reports regarding broccoli by-products, such as leaves, stems, and stalks, although they make up a considerable proportion of a whole broccoli plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation